2013
DOI: 10.1371/journal.pone.0058097
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Visual Processing Speed in Reading Speed Development

Abstract: A steady increase in reading speed is the hallmark of normal reading acquisition. However, little is known of the influence of visual attention capacity on children's reading speed. The number of distinct visual elements that can be simultaneously processed at a glance (dubbed the visual attention span), predicts single-word reading speed in both normal reading and dyslexic children. However, the exact processes that account for the relationship between the visual attention span and reading speed remain to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 65 publications
(106 reference statements)
5
77
2
5
Order By: Relevance
“…It has been previously shown that, for both shallow and deep orthographies, the greater the visual attention span skills, the faster the reading speed Lobier, Dubois, & Valdois, 2013), showing that when several letters are identified simultaneously in one visual attentional capture, the following reading computations are speeded up (e.g., phonological access from print). Therefore, lexical effects on reading speed may be expected across orthographies (see Fig.…”
Section: Predictions Of the Grain Size Accommodation Hypothesismentioning
confidence: 99%
“…It has been previously shown that, for both shallow and deep orthographies, the greater the visual attention span skills, the faster the reading speed Lobier, Dubois, & Valdois, 2013), showing that when several letters are identified simultaneously in one visual attentional capture, the following reading computations are speeded up (e.g., phonological access from print). Therefore, lexical effects on reading speed may be expected across orthographies (see Fig.…”
Section: Predictions Of the Grain Size Accommodation Hypothesismentioning
confidence: 99%
“…
‘A steady increase in reading speed is the hallmark of normal reading acquisition… visual attention capacity could constrain reading speed in elementary school children’ (Lobier, Dubois, & Valdois, , p. 1).
…”
Section: Multi‐trace Memory Model: a Connectionist Model Of Readingmentioning
confidence: 99%
“…Previous studies reported that visual rapid processing played an important role in reading fluency (McLean et al, 2011; Lobier et al, 2012, 2013; Main et al, 2014). Visual rapid processing includes rapid temporal processing and rapid simultaneous processing (Lallier and Valdois, 2010).…”
Section: Introductionmentioning
confidence: 99%